Relationship between betahydroxybutyrate (BHB) and acetone concentrations in postmortem blood and cause of death. (April 2021) - Midtlyng, Lena; Høiseth, Gudrun; Luytkis, Hege; Kristoffersen, Lena; Le Nygaard, Ilah; Strand, Maren Cecilie; Arnestad, Marianne; Vevelstad, Merete
Highlights: Sudden death due to ketoacidosis can be overlooked due to non-specific symptoms. Postmortem diagnosis often depends on analysis of ketone bodies in postmortem blood. We found BHB more sensitive than acetone for detecting significant ketoacidosis. We suggest that BHB should be routinely analyzed in postmortem investigations. Abstract: Unexpected death caused by diabetic or alcoholic ketoacidosis is easily overlooked due to the non-specific symptoms. Although the acid betahydroxybutyrate (BHB) is the most abundant ketone body formed in conditions with ketoacidosis, routine analysis in postmortem investigations often only includes the neutral ketone body acetone. This study aims to evaluate the usefulness of implementing routine BHB analysis in postmortem cases, by investigating the relationship between BHB and acetone concentrations in postmortem blood and the main cause of death. From our database of forensic autopsy cases examined from 2012 to 2015, there were 376 cases with BHB and/or acetone detected in postmortem blood that could be paired with data from the Norwegian Cause of Death Registry. Cases were categorized into three groups based on cause of death: "Diabetes-related" (n = 38), "Alcohol-related" (n = 35) and "Other" (n = 303). Analysis of BHB in blood was performed using UHPLC-MS/MS (limit of quantification (LOQ) 52 mg/L) and of acetone using HS-GC-FID (LOQ 87 mg/L). For the purpose of the study, the acetone method was also validated for a LOQ of 23 mg/L. The median BHB concentration was significantly higher in the group of diabetes-related deaths (671 mg/L, range 68–1311 mg/L) compared to the group of alcohol-related (304 mg/L, range 65–1555 mg/L, p <0.001) and other causes of deaths (113 mg/L, range 0–1402 mg/L, p <0.001). In seven deaths (1.9%), the BHB blood concentration was above the suggested pathological threshold of 250 mg/L, without detection of acetone in blood above 23 mg/L. In 15% of deaths by other causes than diabetes or alcohol, a pathologically significant BHB blood concentration was detected. Our results indicate that BHB is a more reliable marker of pathologically significant ketoacidosis than acetone, and we suggest that BHB should be routinely analyzed in postmortem investigations.